Oral health status for primary dentition - A pilot study - Janvi Manish Gandhi; Deepa Gurunathan; Srisakthi Doraikannan; Arthi Balasubramaniam (Wolters Kluwer Medknow Publications, 2021)
Introduction: Formulating an oral health status which will include oral hygiene index (OHI) exclusively for children, deft index, and the incidence of white spot lesions (WSL) will make it easier for the examiner to assess the current oral health status of a child and help in planning preventive strategies. This index will provide a comprehensive yet quick way to assess the oral health status of children as it includes past caries experience, present oral hygiene status, and future prediction of caries. Materials and Methods: Two hundred children (100 male, 100 female) aged 3-5 years (primary dentition) were included in this study. OHI, recorded index tooth wise and segment wise, deft index, and the WSLs classification were recorded in all the children. Receiver operating characteristics (ROC) curve was used to evaluate the accuracy of recording OHI in children index tooth wise and segment wise. Results: All the three indices were recorded for the 200 subjects, and based on the area under the curve of receiver operating characteristics, it was found that the OHI for primary dentition can be recorded tooth wise or segment wise. Index teeth chosen for primary dentition were labial surfaces of 54, 61, and 64, lingual surfaces of 82, 75, and 85. Conclusion: It includes the past caries experience, present hygiene status, and the future prediction of caries, making it a wholesome index. This cumulative index can be widely used in studies of epidemiology and ensure quicker evaluation during dental health programs in public school systems.